Organisasi Adaptive dalam Pengembanan Kebijakan Pariwisata di Kabupaten Bulukumba - Yuliani, Yuliani; Ansari, Muh Isa; Kasmad, Rulinawaty (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine how the Adaptive Organization in the development of tourims policy in Bulukumba Regency. This study used descriptive Qualitative research, data collection techniques used observation, interviews and documentation. Data analysis techniques used data reduction, data presentation and conclusion. The results of this study showed that the Adaptive Organization in the development of tourims policy still needed a lot of changes, such as changes in technology and could adapt to the environment. Although the strategy was carried out in the development of tourims for the achievement of goals utilizing social media as Genti (Indonesian unit generation).